2021
DOI: 10.1038/s42004-021-00507-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited state dynamics and light-switching of [Ru(phen)2(dppz)]2+ in G-quadruplex DNA

Abstract: The triplet metal to ligand charge transfer (3MLCT) luminescence of ruthenium (II) polypyridyl complexes offers attractive imaging properties, specifically towards the development of sensitive and structure-specific DNA probes. However, rapidly-deactivating dark state formation may compete with 3MLCT luminescence depending on different DNA structures. In this work, by combining femtosecond and nanosecond pump-probe spectroscopy, the 3MLCT relaxation dynamics of [Ru(phen)2(dppz)]2+ (phen = 1,10-phenanthroline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…Furthermore, marked changes in lifetime and emission intensity with different topologies were observed. In contrast to other reported Ru­(II)-based G4 ligands and indeed to Phen-DC3 itself, we have shown using CD titrations that Ru-PDC3 disrupts a variety of G4 structures …”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, marked changes in lifetime and emission intensity with different topologies were observed. In contrast to other reported Ru­(II)-based G4 ligands and indeed to Phen-DC3 itself, we have shown using CD titrations that Ru-PDC3 disrupts a variety of G4 structures …”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to other reported Ru(II)-based G4 ligands and indeed to Phen-DC3 itself, we have shown using CD titrations that Ru-PDC3 disrupts a variety of G4 structures. 64 We also report preliminary studies of the uptake and distribution of Ru-PDC3 in live cells and discuss its prospects as a G4 imaging probe.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more recently, the ultrafast excited state dynamics of [Ru(phen) 2 ( dppz )] 2+ was studied in order to investigate the influence of the microenvironment around the complex on the population of both the bright and dark states [ 198 ]. The ultrafast dark state formation and decay rates are the most sensitive to the amount of water near the complex.…”
Section: Interactions Of Ruthenium(ii) Complexes With G-quadruplexesmentioning
confidence: 99%
“…Luminescent metal complexes, especially iridium(III) complexes, have been employed to detect a range of species due to their high photostability, large Stokes shift, selective luminescence enhancement in the presence of G-quadruplex DNA, and long-lived emission that allows discrimination from fluorescence noise in biological matrices by use of time-resolved techniques [20] , [21] , [22] , [23] , [24] . Our previous studies have demonstrated that iridium(III) complex-based interference reduction biosensing strategies, such as nicking endonuclease-mediated interference reduction rolling circle amplification (NEM-IR-RCA) and interference reduction nucleic acid amplification strategy (IR-NAAS), are suitable for the highly specific detection of target nucleic acid sequences, such as miRNAs and COVID-19 RNAs [18] , [25] .…”
Section: Introductionmentioning
confidence: 99%